SURVEY OF STUDENTS AND TEACHERS OF PHYSICAL EDUCATION ABOUT PHYSICAL ACTIVITY OF PUPILS IN ELEMENTARY SCHOOL - Nela Tatar; Mirza Mulešković; Rajko Ćupić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The aim of this study was to determine whether there is an awareness of the school population about the importance of movement and exercise, engage in sports or recreational activities in their free time or meet the amount of exercise in class, and if there is and how much interest for introduction of additional hours of physical education in the form of compulsory or elective.Data were collected via an anonymous questionnaire, a survey consisted of: data on body weight and height, then, the questions in the questionnaire included the age and gender of respondents, the importance of movement and physical activity for the respondents, doing sport or recreational activity and frequency of practicing respondents, as well as possible reasons for not doing physical activity. Also, questions were whether the fund meets the hours of physical education to their need for exercise and whether they would like to compulsory or elective classes with the larger fund of weekly classes, as well as issues pertaining to the perception of intrinsic motivation, where students responded by circling ratings of sentence on a scale of 1 to 5. The main groups were respodents from VI,VII, VIII and IX class of elementary school from the Capital city, and also their profesors. The results of this survey, ie the existence of negative attitudes toward physical education, can worried us in future work in this social activity and achieving the highest goal of physical education, to take certain steps to form a lasting habit of participation in physical exercise.